Internal Control-Based QR Code Inventory System of Maintenance and Repair Application at Manado State Polytechnic - Susy Marentek; Edwin Lumunon; Esrie Limpeleh; Heidy Pesik (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The implementation of maintenance and repair activities at the Manado State Polytechnic is currently still manual so the evaluation of these activities cannot be monitored properly. Apart from that, reporting of damage to goods and repairs from units and departments is still manual with a letter signed directly and taken to Deputy Director 2 for approval. This will slow down the work process because UPT MR will carry out another evaluation which will then be reported to Deputy Director 2 for improvements. Therefore, we need an application that can make the steps for proposing repairs and maintenance digitally based on a website so that it can be done via a laptop, computer, or Android device. Apart from that, the existing inventory items are not properly recorded. Where no application can display the quantity and condition of goods, whether the goods are in good condition, damaged, or can still be repaired. This inventory process will be created in an integrated application through this system so that agency and unit leaders can monitor the condition and quantity of existing goods directly anywhere. Therefore, this application speeds up the process of collecting data on goods and can also repair all existing goods based on the correct rules and steps. Likewise, leaders can print reports on the condition and quantity of goods at any time for any purpose without needing to search for these data. Apart from this application being able to store data digitally, this application will also speed up and simplify the process of collecting data on goods by simply scanning the QR Code to see data on certain goods. This application will also speed up and make it easier for units and departments to propose repairs and maintenance of goods at the Manado State Polytechnic.